Crack Music: Representations of the Drugs Trade in New York Hip-Hop - Duncan, Andrew (2024)
This thesis offers the first in-depth analysis of Hip-Hop lyrics from New York that discuss the drugs trade. I argue throughout, that Hip-Hop lyrics constitute a discourse of “Black vernacular neoliberalism,” and examine the ways in which performers narrativize the trade in illegal drugs and simultaneously evidence and codify exemplary neoliberal behaviours. New York is the birthplace of Hip-Hop, and the city has frequently found itself at the centre of various drug ‘panics’ from the early twentieth century to the present day. Its status as a major site of financialization has necessitated its close relationship with systems of neoliberal governance. One key policy initiative in this arena has been the ongoing “War on Drugs,” which has disproportionately targeted New York’s black communities. These are often the communities which produce the city’s most famous MCs. As such, Hip-Hop lyrics emerging from this context are adroit at discussing and documenting the business of selling drugs, as well as reflecting on the nature and changing mores of the city as a whole. Central to this process is the figure of the ‘hustler,’ whose consistent and extensive engagement with notions of entrepreneurialism form much of the basis of my analysis. Many rappers seek to collapse their two known businesses – the drugs trade and the music business – arguing that one is a simple reflection of the other. Thus, they claim to be able to move with ease between the illicit and legitimate economies. I examine this frequently utilized rhetorical device in my thesis to understand its accuracies and inaccuracies and unpack the ways in which dealing drugs constitutes an economic education which some individuals are able to segue into extremely successful legitimate ventures. The methodology of this thesis is close textual analysis of song lyrics and their accompanying musical compositions. This analysis is augmented by extensive and wide-ranging interdisciplinary reading on the sociological and criminological realities of the drugs trade in New York between the early 1980s and the early 2000s. This juxtaposition examines the songs as literary texts, exposing and understanding their artifice and construction, but also scrutinizes their claims to be documentarian. Authenticity is loudly and frequently proclaimed within Hip-Hop lyrics, and I seek to understand how accurate the portrayal of the business of selling drugs in these songs is.